2023
DOI: 10.1126/sciadv.adg2324
|View full text |Cite
|
Sign up to set email alerts
|

Boosting internal quantum efficiency via ultrafast triplet transfer to 2H-MoTe 2 film

Abstract: Organic systems often allow to create two triplet spin states (triplet excitons) by converting an initially excited singlet spin state (a singlet exciton). An ideally designed organic/inorganic heterostructure could reach the photovoltaic energy harvest over the Shockley-Queisser (S-Q) limit because of the efficient conversion of triplet excitons into charge carriers. Here, we demonstrate the molybdenum ditelluride (MoTe 2 )/pentacene heterostructure to boost the carrier density via eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Jang et al have demonstrated efficient MEG of MoTe 2 and SEF of pentacene in MoTe 2 /pentacene heterostructure. 36 Unfortunately, although efficient triplet extraction has been achieved by ultrafast electron transfer from pentacene to MoTe 2 , MEGT from MoTe 2 to pentacene through hole transfer occurs on a slow nanosecond scale.…”
Section: Enhanced Materials Explorationmentioning
confidence: 99%
See 2 more Smart Citations
“…Jang et al have demonstrated efficient MEG of MoTe 2 and SEF of pentacene in MoTe 2 /pentacene heterostructure. 36 Unfortunately, although efficient triplet extraction has been achieved by ultrafast electron transfer from pentacene to MoTe 2 , MEGT from MoTe 2 to pentacene through hole transfer occurs on a slow nanosecond scale.…”
Section: Enhanced Materials Explorationmentioning
confidence: 99%
“…MEG processes in 2D semiconductors have been investigated by a few groups using ultrafast spectroscopy techniques. By ultrafast transient absorption spectroscopy covering both visible and mid-IR probe range, Kim et al. have observed highly efficient MEG in MoTe 2 and WSe 2 thin films (∼16.4 nm) with threshold energy close to twice the bandgap and a high conversion efficiency exceeding 93% (Figure b) .…”
Section: Multiexciton Generation In 2d Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jang et al. demonstrated electron transfer from the triplet states in pentacene (triplet energy 0.86 eV) to MoTe 2 (band gap 1.1 eV) doubling the photocurrent in a bilayer device . This type of bilayer solar cells are beneficial for exceeding the Shockley–Queisser limit as the MoTe 2 shows efficient carrier multiplication (QY ≈ 2 for 2 E g < E < 3 E g , where E g is the band gap).…”
mentioning
confidence: 99%
“…demonstrated electron transfer from the triplet states in pentacene (triplet energy 0.86 eV) to MoTe 2 (band gap 1.1 eV) doubling the photocurrent in a bilayer device. 37 This type of bilayer solar cells are beneficial for exceeding the Shockley–Queisser limit as the MoTe 2 shows efficient carrier multiplication (QY ≈ 2 for 2 E g < E < 3 E g , where E g is the band gap). Ye et al have shown for TIPS-pentacene/MoS 2 heterostructure triplets generated by singlet fission dissociate at the interface and transfer electrons to MoS 2 enhancing the photocurrent beyond 100%.…”
mentioning
confidence: 99%